Manajemen Perbankan Syariah di Pasar Rakyat, Pendekatan Berbasis Komunitas - Sofianiyatin, Lilik; Muttaqin, Imam (Proceedings of Annual Conference for Muslim Scholars, 2024)
Sharia banking can significantly contribute to sustainable and inclusive economic growth. This article explores strategies to enhance sharia banking management through a community-based approach in people's markets. By leveraging local market potential, Islamic banks can increase community engagement, strengthen customer relationships, and develop tailored financial products. The research identifies various initiatives, such as financial education programs, collaborations with micro-businesses, and the creation of sharia-compliant financial products. A community-based approach can improve both internal bank management and local economic growth. The article recommends a community-based strategy as a crucial step to enhance sharia banking management in people's markets. It underscores the importance of collaboration between sharia banks and communities to achieve shared goals in sustainable economic development.